2016
DOI: 10.2463/mrms.2015-0006
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Hyperintense Vessels on FLAIR Imaging and Arterial Circulation Time on Cerebral Angiography

Abstract: In cases of large arterial occlusion, the hyperintensity of vessels on FLAIR images may be dependent on arterial circulation time via retrograde filling of the leptomeningeal collateral circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…This study showed that compared with the gold standard DSA grades for PC detection, semiquantitative grading based on TOF-MRAsi has good sensitivity and specificity, and demonstrated that mRS tended to be lower in patients with good PC grades based on TOF-MRAsi, although the relation between PC TOF-MRAsi grade and DWI infarct volume at admission were not significant because the time from the qualifying event to TOF-MRAsi was about 7 days in patients with ischemic stroke. Previous studies have shown that in patients with MCATO with good PC, there is higher vascular signal intensity at the distal end of the MCATO segment in fluid-attenuated inversion recovery sequences, 12 increased cortical branches in the ipsilateral posterior cerebral artery in three-dimensional MRA images, 13 greater difference in blood flow between lesions and the contralateral posterior cerebral artery in quantitative MRA, 14 and lower degree of cerebral blood flow decrease on dynamic magnetic resonance perfusion (MRP) images. 15 These studies indirectly suggest a correlation between TOF-MRAsi and PC.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that compared with the gold standard DSA grades for PC detection, semiquantitative grading based on TOF-MRAsi has good sensitivity and specificity, and demonstrated that mRS tended to be lower in patients with good PC grades based on TOF-MRAsi, although the relation between PC TOF-MRAsi grade and DWI infarct volume at admission were not significant because the time from the qualifying event to TOF-MRAsi was about 7 days in patients with ischemic stroke. Previous studies have shown that in patients with MCATO with good PC, there is higher vascular signal intensity at the distal end of the MCATO segment in fluid-attenuated inversion recovery sequences, 12 increased cortical branches in the ipsilateral posterior cerebral artery in three-dimensional MRA images, 13 greater difference in blood flow between lesions and the contralateral posterior cerebral artery in quantitative MRA, 14 and lower degree of cerebral blood flow decrease on dynamic magnetic resonance perfusion (MRP) images. 15 These studies indirectly suggest a correlation between TOF-MRAsi and PC.…”
Section: Discussionmentioning
confidence: 99%
“…Even if acute ischemic stroke is caused by an occlusion of a cerebral artery, FHVs are not detected when the cerebral blood flow velocity is fast through the collateral circulation [3]. With regard to the clinical meaning of FHVs, distal FHVs reflect the collateral circulation, and the outcome is favorable for distal FHVs in acute ischemic stroke patients [4].…”
Section: Discussionmentioning
confidence: 99%
“…The median age of the cohort was 74 years (interquartile range [IQR], 64-79), and 45% of patients were men. The median NIHSS score was 14 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The median DWI-ASPECTS was 7 (5-8), and 17% of the DWI lesions were positive on FLAIR imaging.…”
Section: Pooled Study Cohortmentioning
confidence: 98%
“…Other studies have described the correlation of FHV with collateral status of conventional angiography in smaller pilot studies. 17 Further, a recent study by Liu et al 18 demonstrated that FHVAlberta Stroke Program Early CT Score (ASPECTS) graded outside of the diffusion-weighted imaging (DWI) lesion was associated with good clinical outcome at discharge and postulated that FHVs are indicative of sufficient collateralization.…”
Section: Strokementioning
confidence: 99%